Simulation and experiments of active vibration control for ultra-long flexible manipulator under impact loads. (February 2019) - Huang, Yi; Liu, Zhiqiang; Du, Ronghua; Tang, Hongbin
This paper aims to reduce the tip vibration of an ultra-long flexible manipulator subjected to impact loads. A modified least mean square method is proposed to determine the frequency response matrix of control paths and identify the complex amplitude of external excitation responses. The presented work is innovative in the sense that: (1) a theoretical model and a new algorithm are proposed for the identification of explicit convergence conditions of online parameters, and they are used to calculate output variables for the optimized robotic control; (2) an active numerical approach is developed to control the response of the tip vibration of the manipulator. The control algorithm is based on a relational model of control parameters and system outcomes; (3) design of experiments is performed for the verification purpose. The active vibration control has been demonstrated on a pump truck product where the third boom hydraulic cylinder is selected as the actuator for testing, and the manipulator tip is equipped with an acceleration sensor to collect the information of vibration; and (4) the performance of the proposed active vibration control has been validated on the flexible manipulator, and the results have shown that the amplitude of the vibration of robotic tip has been decreased for more than 60%.